Adhesive composition for road surface or ground and marking sheet
Patent Information
- Application Number
- CN202180064969.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-10-05
- Filing Date
- 2021-09-29
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2041-09-29
AI Technical Summary
In the prior art, when the road surface or floor surface marking sheet is used in a high temperature environment, the adhesion between the adhesive layer and the substrate increases, resulting in the adhesive remaining on the road surface during peeling, causing pollution, and at the same time, the road surface is lacking. excellent properties of releasing and moisture and heat resistance.
The adhesive composition containing a (meth)acrylic copolymer and a rosin-based tackifying resin is used to crosslink it by crosslinking the crosslinking agent to form excellent adhesiveness, peel resistance, heat resistance and Adhesive layer that is resistant to moisture and heat.
It achieves good follow-up and peelability of the road surface in high temperature and humid environments, avoids adhesive residues, and improves the overall performance of the marker sheet.
Smart Images

Figure CN116368198B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an adhesive composition for pavement or ground and a marking sheet. Background Art
[0002] Road or ground marking sheets are affixed to the road or ground of indoor and outdoor roads, parking lots, etc., and are used on the road or ground of roads, parking lots, etc. (hereinafter sometimes referred to as "road surfaces, etc.") for the purpose of displaying information such as publicity, direction instructions, traffic signs or guidance.
[0003] The marking sheet to be pasted and set on such a road surface, etc. is composed of, for example, a vinyl chloride sheet as a base material, an adhesive layer for pasting to the road surface, etc. on one surface of the base material, and a decorative layer with text or patterns related to the required information formed on the other surface of the base material.
[0004] Road marking sheets are used in an environment where they are exposed to long periods of outdoor wind, rain, and sunshine, and where vehicles repeatedly travel. In addition, ground marking sheets are used in an environment where they are continuously subjected to friction or impact caused by cleaning operations or pedestrians' shoes. Therefore, marking sheets attached to road surfaces may cause the marking sheets themselves to be damaged or peeled off from the road surface.
[0005] On the other hand, when the marking sheet is placed in a high temperature environment for a long time, the adhesive layer of the marking sheet has higher adhesion to the road surface than the substrate. When the marking sheet is peeled off, the adhesive layer will remain on the road surface side, causing the road surface to be contaminated.
[0006] To address such problems, in order to prevent the deterioration of road surface or ground marking sheets, development of adhesives and laminates composed of an adhesive layer and a base material has been underway.
[0007] In addition, the road surface or ground marking sheet usually needs to have adhesion, weather resistance, heat resistance and moisture-heat resistance in addition to the ability to follow the rough surface with uneven surfaces such as asphalt. In addition, in order to show the ability to follow the asphalt, etc., the use of metal substrates such as aluminum is being studied. When using such a metal substrate, as a component of the adhesive layer, it can be considered to copolymerize a monomer having an acidic group that interacts strongly with the metal.
[0008] For example, Patent Document 1 discloses a pressure-sensitive adhesive composition for poorly bonded adherends containing an acrylic resin (A) obtained by copolymerizing a copolymer component (a) of a terminal carboxyl group-containing monomer (a1) and (meth)acrylic acid (a2).
[0009] Patent document 2 discloses a pavement / ground marking sheet consisting of a marking sheet main body and a pavement / ground marking laminate sheet, wherein the marking sheet main body has a first adhesive layer, a metal layer, a second adhesive layer, a substrate and a decorative layer, and the pavement / ground marking laminate sheet is adhered to the surface of the marking sheet main body on the opposite side to the pavement side (first adhesive layer).
[0010] Prior art literature
[0011] Patent Literature
[0012] Patent Document 1: Japanese Patent Application Publication No. 2019-151837
[0013] Patent Document 2: Japanese Patent Application Publication No. 2015-184488 Summary of the invention
[0014] Technical problem to be solved by the invention
[0015] Patent Document 1 exemplifies modified asphalt and the like as adherends of the adhesive tape. However, the adhesive composition of Patent Document 1 does not describe the adhesion between the adhesive layer and the metal layer in a laminate having a metal layer, or the road surface contamination resistance of the adhesive so that the adhesive does not easily transfer to the road surface (asphalt) as the adherend (i.e., the adhesive has excellent removability from the road surface).
[0016] Patent Document 2 discloses a laminated body composed of an adhesive layer using an acrylic adhesive and a base material composed of polyvinyl chloride, an adipic acid polyester plasticizer, a calcium-zinc stabilizer, and a thermoplastic polyurethane elastomer, which has excellent impact mitigation and can maintain good visibility of the decorative layer from the perspective of adhesion and durability. However, there is no description of removability from the road surface.
[0017] Technical Problem to be Solved by the Present Invention In view of the above-mentioned problems, an object of the present invention is to provide an adhesive composition which, in addition to having good conformability to rough road surfaces such as asphalt, also has excellent adhesion, peeling resistance, heat resistance and moisture-heat resistance, excellent adhesion between the substrate and the adhesive layer, and can inhibit the adhesive from being transferred from the substrate to the adherend during peeling.
[0018] Solutions to technical problems
[0019] The present inventors have conducted intensive studies to solve the above-mentioned technical problems and have found that a PSA composition containing a specific (meth)acrylic copolymer and a specific tackifier resin in specific amounts can solve the above-mentioned technical problems, thereby completing the present invention.
[0020] The present invention relates to, for example, the following [1] to [7].
[0021] [1] An adhesive composition for road surfaces or floors, comprising a (meth)acrylic copolymer (A) and a rosin-based tackifier resin (B), wherein the (meth)acrylic copolymer (A) is a copolymer comprising monomer components of 20 to 69% by mass of a (meth)acrylic acid alkyl ester monomer (a1) having an alkyl carbon number of 1 to 7, 30 to 74% by mass of a (meth)acrylic acid alkyl ester monomer (a2) having an alkyl carbon number of 8 to 20, and 1 to 6% by mass of an acidic group-containing monomer (a3), wherein the total of components (a1) to (a3) is 100% by mass, the content of the rosin-based tackifier resin (B) is 10 to 30 parts by mass relative to 100 parts by mass of the (meth)acrylic copolymer (A), and the proportion of components having a molecular weight of 5,000 or less in the (meth)acrylic copolymer (A) is 1.5% by mass or less.
[0022] [2] The road surface or floor adhesive composition according to [1] above, wherein the rosin-based tackifier resin has a softening point of 120° C. or higher.
[0023] [3] The adhesive composition for road surfaces or floors according to [1] or [2], further comprising a crosslinking agent (C).
[0024] [4] A road surface or ground marking sheet comprising an adhesive layer formed from the adhesive composition according to any one of [1] to [3] above and a metal substrate.
[0025] [5] The road surface or ground marking sheet according to [4] above, wherein the metal substrate is aluminum foil.
[0026] [6] The road surface or ground marking sheet as described in [4] or [5] above, further comprising a plastic substrate.
[0027] [7] The road surface or ground marking sheet as described in [6] above, wherein the plastic substrate is at least one substrate selected from polyvinyl chloride, polyethylene terephthalate, polyethylene and polyimide.
[0028] Effects of the Invention
[0029] According to the present invention, an adhesive composition can be provided which has excellent adhesion, peeling resistance, heat resistance and moisture-heat resistance in addition to the ability to follow rough surfaces such as asphalt roads, and has excellent adhesion between the substrate and the adhesive layer, and can inhibit the adhesive from being transferred from the substrate to the adherend during peeling. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a schematic diagram showing a specific example of the layer structure of the marking sheet of the present invention. DETAILED DESCRIPTION
[0031] Hereinafter, the present invention will be described in detail.
[0032] In the present specification, (meth)acrylic acid is used as a general term for acrylic acid and methacrylic acid, and may be either acrylic acid or methacrylic acid. (meth)acrylate is also used as a general term for acrylate and methacrylate, and may be either acrylate or methacrylate.
[0033] [Adhesive composition for road surface or floor]
[0034] The adhesive composition for road surfaces or floors of the present invention (hereinafter sometimes simply referred to as "adhesive composition") comprises a (meth)acrylic copolymer (A) and a rosin-based tackifier resin (B) which are described below.
[0035] <(Meth)acrylic acid-based copolymer (A)>
[0036] The (meth)acrylic copolymer (A) is a copolymer containing monomer components of 20 to 69% by mass of a (meth)acrylic acid alkyl ester monomer (a1) having an alkyl group carbon number of 1 to 7, 30 to 74% by mass of a (meth)acrylic acid alkyl ester monomer (a2) having an alkyl group carbon number of 8 to 20, and 1 to 6% by mass of an acidic group-containing monomer (a3).
[0037] 《(Meth)acrylic acid alkyl ester monomer (a1)》
[0038] The (meth)acrylic copolymer (A) comprises a (meth)acrylic acid alkyl ester monomer (a1) having an alkyl group with 1 to 7 carbon atoms (hereinafter also referred to as "monomer (a1)").
[0039] Examples of the alkyl group having 1 to 7 carbon atoms include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, sec-butyl, n-pentyl, isopentyl, neopentyl, n-hexyl, 1-methylpentyl, 4-methyl-2-pentyl, 3,3-dimethylbutyl, 2-ethylbutyl and n-heptyl. The alkyl group may be straight chain or branched.
[0040] Examples of the monomer (a1) having an alkyl group with 1 to 7 carbon atoms include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, isobutyl (meth)acrylate, n-butyl (meth)acrylate, tert-butyl (meth)acrylate, sec-butyl (meth)acrylate, n-pentyl (meth)acrylate, neopentyl (meth)acrylate, isopentyl (meth)acrylate, n-hexyl (meth)acrylate and n-heptyl (meth)acrylate.
[0041] Among them, n-butyl (meth)acrylate and t-butyl (meth)acrylate are preferred as the monomer (a1).
[0042] The monomer (a1) may be used alone or in combination of two or more.
[0043] 《(Meth)acrylic acid alkyl ester monomer (a2)》
[0044] The (meth)acrylic copolymer (A) contains an alkyl (meth)acrylate monomer (a2) having an alkyl group with 8 to 20 carbon atoms (hereinafter also referred to as “monomer (a2)”).
[0045] Examples of the alkyl group having 8 to 20 carbon atoms include 2-ethylhexyl, n-octyl, isooctyl, 1-methylheptyl, n-decyl, isodecyl, 2-propylpentyl, n-nonyl, 2,2-dimethylheptyl, 2,6-dimethyl-4-heptyl, 3,5,5-trimethylhexyl, n-undecyl, 1-methyldecyl, n-dodecyl, n-tridecyl, 1-hexylheptyl, n-tetradecyl, n-pentadecyl, n-hexadecyl, n-heptadecyl, n-octadecyl, and n-eicosyl. The above alkyl groups may be straight chain or branched.
[0046] Examples of the monomer (a2) having an alkyl group with 8 to 20 carbon atoms include 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, octadecyl (meth)acrylate, isooctadecyl (meth)acrylate, n-nonadecyl (meth)acrylate, isononadecyl (meth)acrylate and n-eicosyl (meth)acrylate.
[0047] Among them, preferred monomers (a2) are 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, and isooctyl (meth)acrylate.
[0048] The monomer (a2) may be used alone or in combination of two or more.
[0049] In the monomer components, the mass ratio of monomer (a1) to monomer (a2) is preferably 1:0.6 to 1:2.2, and more preferably 1:0.7 to 1:1.5. The adhesive composition comprising the (meth)acrylic copolymer (A) using monomer (a1) and monomer (a2) in the above range has excellent balance between adhesion and cohesion with the substrate.
[0050] 《Acidic group-containing monomer (a3)》
[0051] The (meth)acrylic copolymer (A) contains an acidic group-containing monomer (a3) (hereinafter also referred to as “monomer (a3)”).
[0052] The acidic group-containing monomer (a3) may, for example, be a carboxyl group-containing monomer, a sulfonic acid group-containing monomer or a phosphoric acid group-containing monomer, and a carboxyl group-containing monomer is preferred.
[0053] The carboxyl group-containing monomer is a monomer having a carboxyl group in the molecule. Specific examples of the carboxyl group-containing monomer include acrylic acid, methacrylic acid, β-carboxyethyl (meth)acrylate, 5-carboxypentyl (meth)acrylate, succinic acid mono(meth)acryloyloxyethyl ester, ω-carboxy polycaprolactone mono(meth)acrylate, crotonic acid, maleic acid, fumaric acid, itaconic acid, citraconic acid, and the like.
[0054] The sulfonic acid group-containing monomer is a monomer having a sulfonic acid group in the molecule. Specific examples of the sulfonic acid group-containing monomer include styrene sulfonic acid, allyl sulfonic acid, (meth)acrylic acid sulfonate propyl ester, 2-(meth)acrylamide-2-methylpropanesulfonic acid, (meth)acrylamidepropanesulfonic acid, and (meth)acryloyloxynaphthalenesulfonic acid.
[0055] The phosphoric acid group-containing monomer is a monomer having a phosphoric acid group in the molecule. Specific examples of the phosphoric acid group-containing monomer include 2-hydroxyethyl acryloyl phosphate.
[0056] Among them, as the monomer (a3), at least one monomer selected from acrylic acid, methacrylic acid, and β-carboxyethyl (meth)acrylate is preferably used, and at least one monomer selected from acrylic acid and methacrylic acid is more preferably used. These monomers are easily available industrially and are therefore preferred.
[0057] The monomer (a3) may be used alone or in combination of two or more.
[0058] <Monomer Components of (Meth)Acrylic Copolymer (A)>
[0059] The monomer components constituting the (meth)acrylic copolymer (A) are 20 to 69% by mass, preferably 25 to 63.5% by mass, more preferably 30 to 58% by mass of an alkyl (meth)acrylate monomer (a1), 30 to 74% by mass, preferably 35 to 69% by mass, more preferably 40 to 65% by mass of an alkyl (meth)acrylate monomer (a2), and 1 to 6% by mass, preferably 1.5 to 6% by mass, more preferably 2 to 5% by mass of an acidic group-containing monomer (a3). The total of the components (a1) to (a3) is 100% by mass.
[0060] By using monomer (a1) and monomer (a2) in the above range, an adhesive composition having excellent balance of adhesion and cohesion can be obtained. In addition, the adhesive composition using the acidic monomer (a3) in the above range has improved heat resistance, moisture-heat resistance, and adhesion to metal substrates, so it is preferred. If the monomer (a3) in the (methyl) acrylic copolymer (A) exceeds the above range, when the marking sheet using the adhesive composition is peeled off from the road surface, the re-peelability is poor due to the large amount of glue residue on the road surface, so it is not preferred.
[0061] In addition, the (meth)acrylic copolymer (A) prepared by using each monomer in the above range has excellent compatibility with the rosin-based tackifier resin (B), and the adhesive layer formed from the adhesive composition of the present invention is considered to have the rosin-based tackifier resin (B) dispersed throughout the layer. Since the rosin-based tackifier resin (B) is dispersed throughout the layer, the adhesive layer has excellent stress relaxation properties and heat resistance.
[0062] 《Other monomers (a4)》
[0063] The (meth)acrylic polymer (A) may further contain other monomers (a4) other than the above-mentioned monomers (a1) to (a3). Examples of other monomers (a4) include hydroxyl-containing monomers, alicyclic hydrocarbon group- or aromatic hydrocarbon group-containing (meth)acrylates, alkoxypolyalkylene glycol mono(meth)acrylates, styrene-based monomers, amide group-containing monomers, amino group-containing monomers, cyano group-containing monomers, and vinyl acetate.
[0064] Examples of the hydroxyl-containing monomer include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxyundecyl (meth)acrylate, (4-hydroxymethylcyclohexyl) methacrylate, N-hydroxymethyl (meth)acrylamide, vinyl alcohol, allyl alcohol, 2-hydroxyethyl vinyl ether, and 4-hydroxybutyl vinyl ether. Among them, 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate are preferably used.
[0065] Examples of the (meth)acrylate containing an alicyclic hydrocarbon group or an aromatic hydrocarbon group include cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, adamantyl (meth)acrylate, benzyl (meth)acrylate, phenyl (meth)acrylate and phenoxyethyl (meth)acrylate.
[0066] Examples of the alkoxypolyalkylene glycol mono(meth)acrylate include methoxydiethylene glycol mono(meth)acrylate, methoxydipropylene glycol mono(meth)acrylate, ethoxytriethylene glycol mono(meth)acrylate, ethoxydiethylene glycol mono(meth)acrylate and methoxytriethylene glycol mono(meth)acrylate.
[0067] Examples of the styrene monomer include styrene; alkyl styrenes such as methylstyrene, dimethylstyrene, trimethylstyrene, propylstyrene, butylstyrene, hexylstyrene, heptylstyrene and octylstyrene; halogenated styrenes such as fluorostyrene, chlorostyrene, bromostyrene and dibromostyrene; and functionalized styrenes such as nitrostyrene, acetylstyrene and methoxystyrene.
[0068] Examples of amide group-containing monomers include: N-alkyl (meth)acrylamide such as (meth)acrylamide, N-methyl (meth)acrylamide, N-ethyl (meth)acrylamide, N-propyl (meth)acrylamide, and N-hexyl (meth)acrylamide; N,N-dialkyl (meth)acrylamide such as N,N-dimethyl (meth)acrylamide and N,N-diethyl (meth)acrylamide; and nitrogen-containing heterocyclic monomers such as N-vinyl pyrrolidone, N-vinyl caprolactam, and (meth)acryloylmorpholine.
[0069] As the amino group-containing monomer, N,N-dialkylaminoalkyl (meth)acrylate such as N,N-dimethylaminoethyl (meth)acrylate and N,N-diethylaminoethyl (meth)acrylate may be mentioned.
[0070] As the cyano group-containing monomer, cyano(meth)acrylate and (meth)acrylonitrile may be mentioned.
[0071] The monomer (a4) may be used alone or in combination of two or more.
[0072] The monomer (a4) is an optional component, and the content of the monomer (a4) in 100% by mass of the monomer components for forming the copolymer (A) is preferably 20% by mass or less, more preferably 15% by mass or less, and further preferably 10% by mass or less.
[0073] <Physical Properties of (Meth)Acrylic Copolymer (A)>
[0074] The weight average molecular weight (Mw) of the (meth)acrylic copolymer (A) is preferably 200,000 to 1.5 million, more preferably 250,000 to 1.3 million, and further preferably 350,000 to 1.2 million. Mw within the above range provides sufficient cohesive force to the adhesive sheet obtained from the adhesive composition, and is therefore preferred from the perspective of improving durability under high temperature conditions or high temperature and high humidity conditions.
[0075] The weight average molecular weight (Mw) is measured by gel permeation chromatography (GPC method). The measurement conditions of GPC are described in detail in the Examples section described later.
[0076] The molecular weight distribution (Mw / Mn) of the (meth)acrylic copolymer (A) measured by GPC is preferably 2 to 13, more preferably 2.5 to 10, and further preferably 2.8 to 8. Mw / Mn within the above range is preferred from the viewpoint of durability and removability.
[0077] The ratio of the (meth) acrylic copolymer (low molecular weight component) with a molecular weight of 5000 or less in the (meth) acrylic copolymer (A) is preferably 1.5 mass % or less, more preferably 1.0 mass % or less, and particularly preferably 0.6 mass % or less. The lower limit of the ratio of the component with a molecular weight of 5000 or less is not particularly limited, but is usually 0.01 mass % or more. In addition, the above ratio is the ratio of the component with a molecular weight of 5000 or less when the total molecular weight of the (meth) acrylic copolymer (A) is 100 mass %. The above ratio can be measured by obtaining an integral molecular weight distribution curve by the GPC method. The ratio of the component with a molecular weight of 5000 or less in the (meth) acrylic copolymer (A) can obtain a road surface or ground marking sheet with less glue residue on the road surface and excellent re-peelability within the above range. The ratio of the component with a molecular weight of 5000 or less exceeds 1.5 mass %, and when the adhesive sheet is pasted on the adherend, it is easy to form a layer from the above low molecular weight component on the adhesive layer and the adherend interface and cause adhesion and heat resistance to reduce, so it is not preferred.
[0078] <Production of (meth)acrylic acid-based copolymer (A)>
[0079] The (meth)acrylic copolymer (A) can be produced by a conventionally known polymerization method such as solution polymerization, bulk polymerization, emulsion polymerization, and suspension polymerization, among which solution polymerization is preferred.
[0080] Specifically, monomer components and chain transfer agents and polymerization solvents used as needed are added to a reaction vessel, and a polymerization initiator is added under an inert gas atmosphere such as nitrogen, and the reaction starting temperature is set to usually 40 to 100° C., preferably 50 to 80° C., and the reaction system is maintained at a temperature of usually 50 to 90° C., preferably 60 to 90° C. for 2 to 20 hours. In addition, during the polymerization reaction, polymerization initiators, chain transfer agents, monomer components, and polymerization solvents may be appropriately added. As polymerization initiators, azo initiators and peroxide polymerization initiators may be mentioned.
[0081] Examples of the azo initiator include 2,2'-azobisisobutyronitrile, 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2-cyclopropylpropionitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2-(carbamoylazo)isobutyronitrile, 2-phenylazo-4-methoxy-2,4-dimethyl Azo compounds include 2,2'-azobis(2-aminobispropane) dihydrochloride, 2,2'-azobis(N,N'-dimethylisobutylamidine), 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)-propionamide], 2,2'-azobis(isobutylamide) dihydrate, 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-cyanopropanol), and dimethyl-2,2'-azobis(2-methylpropionate).
[0082] Examples of the peroxide polymerization initiator include tert-butyl hydroperoxide, cumene hydroperoxide, dicumyl peroxide, benzoyl peroxide, lauroyl peroxide, hexanoyl peroxide, diisopropyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, tert-butyl peroxypivalate, 2,2-bis(4,4-di-tert-butylperoxycyclohexyl)propane, 2,2-bis(4,4-di-tert-amylperoxycyclohexyl)propane, 2,2-bis(4,4-di-tert-octylperoxycyclohexyl)propane, 2,2-bis(4,4-di-α-isopropylphenylperoxycyclohexyl)propane, 2,2-bis(4,4-di-tert-butylperoxycyclohexyl)butane, and 2,2-bis(4,4-di-tert-octylperoxycyclohexyl)butane.
[0083] The polymerization initiator may be used alone or in combination of two or more.
[0084] In the production of the (meth)acrylic copolymer (A), the amount of the polymerization initiator used is usually in the range of 0.001 to 5 parts by mass, preferably 0.005 to 3 parts by mass, based on 100 parts by mass of the total monomer components for forming the (meth)acrylic copolymer (A).
[0085] Examples of the chain transfer agent include 2-mercaptoethanol, thioglycerol, 3-mercapto-1-hexanol, mercaptoglycolic acid, 2-mercaptopropionic acid, 3-mercaptopropionic acid, 4-mercaptobutyric acid, 6-mercaptohexanoic acid, 11-mercaptoundecanoic acid, 3-mercaptopyruvic acid, 2-mercaptobenzoic acid, 3-mercaptobenzoic acid, 4-mercaptobenzoic acid, thiomalic acid, n-dodecyl mercaptan, pentaerythritol tetrakis(3-mercaptopropionate), α-methylstyrene dimer, and naphthoquinone compounds.
[0086] The chain transfer agent may be used alone or in combination of two or more.
[0087] When a chain transfer agent is used, the amount of the chain transfer agent used is preferably within a range of 0.01 to 5 parts by mass, more preferably 0.02 to 3 parts by mass, and even more preferably 0.03 to 2.5 parts by mass, based on 100 parts by mass of the monomer components for forming the (meth)acrylic copolymer (A).
[0088] The polymerization solvent used in the solution polymerization includes, for example, aromatic hydrocarbons such as benzene, toluene and xylene; aliphatic hydrocarbons such as n-pentane, n-hexane, n-heptane and n-octane; alicyclic hydrocarbons such as cyclopentane, cyclohexane, cycloheptane and cyclooctane; ethers such as diethyl ether, diisopropyl ether, 1,2-dimethoxyethane, dibutyl ether, tetrahydrofuran, dioxane, anisole, phenethyl ether and diphenyl ether; halogenated hydrocarbons such as chloroform, carbon tetrachloride, 1,2-dichloroethane and chlorobenzene; esters such as ethyl acetate, propyl acetate, butyl acetate and methyl propionate; ketones such as acetone, methyl ethyl ketone, diethyl ketone, methyl isobutyl ketone and cyclohexanone; amides such as N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone; nitriles such as acetonitrile and benzonitrile; sulfoxides such as dimethyl sulfoxide and cyclopentane sulfone, etc.
[0089] The polymerization solvent may be used alone or in combination of two or more.
[0090] <Rosin-based tackifier resin (B)>
[0091] The rosin-based tackifier resin (B) may be any resin having a softening point of 120°C or higher, but the softening point is preferably 120 to 200°C, more preferably 120 to 160°C, from the viewpoint of imparting stress relaxation properties in a high temperature environment.
[0092] Examples of the rosin-based tackifier resin (B) having a softening point of 120°C or higher include PENSEL C (softening point 120°C), PENSEL D-125 (softening point 125°C), PENSEL D-135 (softening point 135°C), PENSEL D-160 (softening point 160°C), and SUPER ESTER A-125 (softening point 125°C) manufactured by Arakawa Chemical Industries, Ltd. Also included are HARITACK PCJ (softening point 123°C), HARITACK DP-2669 (softening point 135°C), and HARITACK FK125 (softening point 125°C) manufactured by Harima Chemicals, Inc.
[0093] The adhesive composition of the present invention contains both the (meth)acrylic copolymer (A) and the rosin resin (B) in specific amounts. Therefore, the adhesive layer obtained from the adhesive composition has little adhesive residue when peeled from a road surface, and has excellent re-peelability from a road surface.
[0094] In the adhesive composition of the present invention, the content of the rosin-based tackifier resin (B) is 10 to 30 parts by mass, preferably 18 to 28 parts by mass, and more preferably 20 to 26 parts by mass, based on 100 parts by mass of the (meth)acrylic copolymer (A).
[0095] <Crosslinking agent (C)>
[0096] The adhesive composition of the present invention preferably contains a crosslinking agent (C) in addition to the (meth)acrylic copolymer (A) and the rosin-based tackifier resin (B). For example, the adhesive composition can be obtained by crosslinking the (meth)acrylic copolymer (A) with the crosslinking agent (C).
[0097] The crosslinking agent can be used without particular limitation, and for example, an isocyanate crosslinking agent, a metal chelate crosslinking agent, or an epoxy crosslinking agent can be used. As the crosslinking agent (C), one type may be used alone, or two or more types may be used in combination.
[0098] As the crosslinking agent (C), at least one selected from an isocyanate crosslinking agent (C-1) and a metal chelate crosslinking agent (C-2) is preferred, and an isocyanate crosslinking agent (C-1) or a metal chelate crosslinking agent (C-2) is preferred, and an isocyanate crosslinking agent (C-1) is more preferred. As the crosslinking agent (C), an isocyanate crosslinking agent (C-1) is preferred because of its excellent adhesion between the adhesive layer and the substrate, and a metal chelate crosslinking agent (C-2) is preferred because it can shorten the aging time.
[0099] 《Isocyanate crosslinking agent (C-1)》
[0100] As the isocyanate crosslinking agent (C-1), an isocyanate crosslinking agent having 2 or more isocyanate groups in one molecule is generally used. By crosslinking the (meth)acrylic copolymer (A) with the isocyanate crosslinking agent (C-1), a crosslinked body (network polymer) can be formed.
[0101] The number of isocyanate groups of the isocyanate crosslinking agent (C-1) is usually 2 or more, preferably 2 to 8, and more preferably 3 to 6. The number of isocyanate groups within the above range is preferred from the perspective of the crosslinking reaction efficiency between the (meth)acrylic copolymer (A) and the isocyanate crosslinking agent (C-1) and the perspective of maintaining the flexibility of the adhesive layer.
[0102] Examples of the diisocyanate crosslinking agent having two isocyanate groups in one molecule include aliphatic diisocyanates, alicyclic diisocyanates, and aromatic diisocyanates. Examples of the aliphatic diisocyanates include aliphatic diisocyanates having 4 to 30 carbon atoms, such as ethylene diisocyanate, tetramethylene diisocyanate, pentamethylene diisocyanate, hexamethylene diisocyanate, 2-methyl-1,5-pentane diisocyanate, 3-methyl-1,5-pentane diisocyanate, and 2,2,4-trimethyl-1,6-hexamethylene diisocyanate.
[0103] Examples of the alicyclic diisocyanate include alicyclic diisocyanates having 7 to 30 carbon atoms, such as isophorone diisocyanate, cyclopentyl diisocyanate, cyclohexyl diisocyanate, hydrogenated xylene diisocyanate, hydrogenated toluene diisocyanate, hydrogenated diphenylmethane diisocyanate, and hydrogenated tetramethylxylene diisocyanate.
[0104] Examples of the aromatic diisocyanate include aromatic diisocyanates having 8 to 30 carbon atoms, such as phenylene diisocyanate, toluene diisocyanate, xylene diisocyanate, naphthalene diisocyanate, diphenyl ether diisocyanate, diphenylmethane diisocyanate and diphenylpropane diisocyanate.
[0105] Examples of the isocyanate crosslinking agent having 3 or more isocyanate groups in one molecule include aromatic polyisocyanates, aliphatic polyisocyanates, and alicyclic polyisocyanates. Specifically, examples include 2,4,6-triisocyanatotoluene, 1,3,5-triisocyanatobenzene, and 4,4',4"-triphenylmethane triisocyanate.
[0106] In addition, examples of the isocyanate crosslinking agent (C-1) include: polymers (e.g., dimers or trimers, biuret bodies, isocyanurate bodies) of the above-mentioned isocyanate crosslinking agents having 2 or 3 or more isocyanate groups, derivatives (e.g., addition reaction products of polyols and 2 or more molecules of diisocyanate crosslinking agents), and polymers. Examples of the polyols in the above-mentioned derivatives include trivalent or higher alcohols such as trimethylolpropane, glycerol, and pentaerythritol as low molecular weight polyols; and examples of high molecular weight polyols include polyether polyols, polyester polyols, acrylic polyols, polybutadiene polyols, and polyisoprene polyols.
[0107] Examples of such isocyanate crosslinking agents include trimers of diphenylmethane diisocyanate, polymethylene polyphenyl polyisocyanates, biuret forms or isocyanurate forms of hexamethylene diisocyanate or toluene diisocyanate, reaction products of trimethylolpropane with toluene diisocyanate or xylene diisocyanate (e.g., 3-molecule adducts of toluene diisocyanate or xylene diisocyanate), reaction products of trimethylolpropane with hexamethylene diisocyanate (e.g., 3-molecule adducts of hexamethylene diisocyanate), polyether polyisocyanates, and polyester polyisocyanates.
[0108] Among the isocyanate crosslinking agents (C-1), reaction products of trimethylolpropane and toluene diisocyanate (such as L-45K manufactured by Soken Chemical Industry Co., Ltd.), reaction products of trimethylolpropane and xylene diisocyanate (such as TD-75 manufactured by Soken Chemical Industry Co., Ltd.), and isocyanurates of hexamethylene diisocyanate or toluene diisocyanate (such as TSE-100 manufactured by Asahi Kasei Corporation and CORONATE 2050 manufactured by Tosoh Corporation) are preferred from the viewpoint of good balance of adhesive properties and high durability.
[0109] The isocyanate crosslinking agent (C-1) may be used alone or in combination of two or more.
[0110] In the adhesive composition of the present invention, the content of the isocyanate crosslinking agent (C-1) is preferably 1 to 5 parts by mass, more preferably 1.2 to 4.5 parts by mass, and even more preferably 1.5 to 4 parts by mass, based on 100 parts by mass of the solid content of the (meth)acrylic copolymer (A).
[0111] 《Metal Chelate Crosslinker (C-2)》
[0112] Examples of the metal chelate crosslinking agent (C-2) include compounds in which alkoxide, acetylacetone, ethyl acetoacetate, etc. are coordinated to a polyvalent metal such as aluminum, iron, copper, zinc, tin, titanium, nickel, antimony, magnesium, vanadium, chromium, zirconium, etc.
[0113] Among them, aluminum chelate compounds (such as M-5ADT manufactured by Soken Chemical Co., Ltd.) are particularly preferred. Specific examples include aluminum isopropoxide, aluminum sec-butyrate, aluminum acetoethyl diisopropoxide, aluminum triacetoethyl, and aluminum triacetylacetonate.
[0114] The metal chelate cross-linking agent (C-2) may be used alone or in combination of two or more.
[0115] In the adhesive composition of the present invention, the content of the metal chelate crosslinking agent (C-2) is preferably 0 to 1 part by mass, more preferably 0 to 0.5 part by mass, and even more preferably 0 to 0.2 part by mass, based on 100 parts by mass of the (meth)acrylic copolymer (A).
[0116] 《Epoxy crosslinking agent (C-3)》
[0117] As the epoxy crosslinking agent (C-3), an epoxy compound having 2 or more epoxy groups in one molecule is generally used. For example, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerol diglycidyl ether, glycerol triglycidyl ether, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, N,N,N',N'-tetraglycidyl meta-xylene diamine, N,N,N',N'-tetraglycidylaminophenylmethane, triglycidyl isocyanurate, meta-N,N-diglycidylaminophenylglycidyl ether, N,N-diglycidyltoluidine, and N,N-diglycidylaniline. The epoxy crosslinking agent (C-3) may be used alone or in combination of two or more.
[0118] In the adhesive composition of the present invention, the content of the epoxy crosslinking agent (C-3) is preferably 0.01 to 1 part by mass, more preferably 0.03 to 0.8 part by mass, and even more preferably 0.05 to 0.5 part by mass, based on 100 parts by mass of the (meth)acrylic copolymer (A).
[0119] In the pressure-sensitive adhesive composition of the present invention, the content of the crosslinking agent (C) is 0.01 to 5 parts by mass, preferably 0.03 to 4.5 parts by mass, and more preferably 0.05 to 4 parts by mass, based on 100 parts by mass of the (meth)acrylic copolymer (A).
[0120] <Other ingredients>
[0121] 《Tackifying resin (D)》
[0122] The adhesive composition of the present invention may further contain a tackifier resin (D) other than the rosin-based tackifier resin (B) having a softening point of 120° C. or higher as an optional component. The tackifier resin (D) is not particularly limited as long as it is a resin other than the rosin-based tackifier resin (B).
[0123] In the adhesive composition of the present invention, the content of the tackifier resin (D) is preferably 0 to 10 parts by mass, more preferably 0 to 8 parts by mass, further preferably 0 to 6 parts by mass, and particularly preferably 0 to 5 parts by mass, relative to 100 parts by mass of the (meth) acrylic copolymer (A). In addition, from the perspective of stress relaxation, cohesion and viscosity at high temperatures, the adhesive composition of the present invention preferably does not substantially contain a tackifier resin (D). Substantially free means that the adhesive composition contains 0 parts by mass or more and less than 0.01 parts by mass of a tackifier resin (D) relative to 100 parts by mass of the (meth) acrylic copolymer (A).
[0124] Examples of the tackifier resin (D) include at least one selected from styrene resins, C9 petroleum resins, hydrogenated petroleum resins, terpene resins, phenolic resins, and rosin-based tackifier resins having a softening point of less than 120° C. The tackifier resin (D) may be used alone or in combination of two or more.
[0125] In addition, the amount of tackifier resin contained in the adhesive composition of the present invention, that is, the total amount of rosin-based tackifier resin (B) and tackifier resin (D) is preferably within the following range. In the adhesive composition of the present invention, the content of tackifier resin is preferably more than 16 parts by mass and less than 35 parts by mass, more preferably 18 to 33 parts by mass, and particularly preferably 20 to 30 parts by mass, relative to 100 parts by mass of (meth)acrylic copolymer (A). Within the above range, it is compatible with (meth)acrylic copolymer (A), exhibits high bonding performance to low-polarity adherends such as olefins, and has high stress relaxation properties, so it is preferred.
[0126] 《Additives (E)》
[0127] The adhesive composition of the present invention may further contain, in addition to the (meth)acrylic copolymer (A) and the rosin-based tackifying resin (B), one or more additives such as a silane coupling agent, an antistatic agent, an antioxidant, a light stabilizer, a metal corrosion inhibitor, a plasticizer, a crosslinking accelerator, a surfactant, a (meth)acrylic copolymer other than the above (A), and a reprocessing agent, as required, within the range not impairing the effects of the present invention.
[0128] When the pressure-sensitive adhesive composition of the present invention contains other components, the amount of the other components is appropriately determined depending on the type thereof, but is usually 0.1 to 30 parts by mass, preferably 0.5 to 20 parts by mass, based on 100 parts by mass of the (meth)acrylic copolymer (A).
[0129] 《Organic solvents (F)》
[0130] The adhesive composition of the present invention preferably contains an organic solvent (F) in order to adjust its coating properties. As the organic solvent (F), the polymerization solvent described in the column <(meth)acrylic copolymer (A)> can be cited. In the adhesive composition of the present invention, the content of the organic solvent is usually 20 to 90% by mass, preferably 30 to 90% by mass, relative to 100% by mass of the adhesive composition.
[0131] In the present specification, “solid content” refers to all components in the adhesive composition except the organic solvent (F), and “solid content concentration” refers to the ratio of the solid content relative to 100% by mass of the adhesive composition.
[0132] In the adhesive composition of the present invention, the amount of the (meth)acrylic copolymer (A) is usually 60% by mass or more, preferably 65% by mass or more, and more preferably 70% by mass or more in 100% by mass of the solid content. The upper limit of the above-mentioned total amount can be appropriately determined according to the amount of other components such as the rosin-based tackifying resin (B) and the crosslinking agent (C).
[0133] <Preparation of Adhesive Composition>
[0134] The adhesive composition of the present invention can be prepared, for example, by mixing the (meth)acrylic copolymer (A), the rosin-based tackifier resin (B), the crosslinking agent (C), and other components as required by a conventionally known method.
[0135] For example, the adhesive composition can be prepared by mixing and stirring a solution containing a (meth)acrylic acid copolymer (A) obtained when synthesizing the (meth)acrylic acid copolymer (A), a rosin-based tackifier resin (B), a crosslinking agent (C), and other components used as needed together or in sequence using a stirring device, etc. The stirring time is not particularly limited, but from the perspective of operability and productivity, it can be carried out at room temperature for about 10 to 120 minutes.
[0136] [Road or ground marking sheet]
[0137] <Structure of road surface or ground marking sheet>
[0138] The road surface or ground marking sheet of the present invention (hereinafter referred to as "the marking sheet of the present invention") comprises an adhesive layer formed from the adhesive composition of the present invention and a metal substrate, wherein the adhesive layer and the metal substrate are laminated.
[0139] As a preferred structure of the marking sheet of the present invention, a first adhesive layer, a first substrate, a second adhesive layer and a second substrate can be exemplified, and these can be stacked in sequence. In addition, the adhesive layer and the substrate can be stacked in the order of a third adhesive layer, a third substrate, a fourth adhesive layer and a fourth substrate on the second substrate, and a decorative layer or a protective layer can be provided in addition.
[0140] Figure 1 It is a schematic diagram showing a specific example of the layer structure of the marking sheet of the present invention. Figure 1 The marking sheet shown has a structure in which a first adhesive layer 11, a first substrate 12 composed of a metal substrate, a second adhesive layer 13, a second substrate 14 composed of polyvinyl chloride, a third adhesive layer 15, and a third substrate 16 composed of polyimide are stacked in this order from an adherend or a release liner 10 along the thickness direction of the marking sheet.
[0141] The surface to be attached to the road surface is usually provided with a release liner. When the marking sheet of the present invention is placed on the road surface, the release liner is peeled off from the first adhesive layer and the marking sheet is attached to a predetermined position on the road surface via the first adhesive layer.
[0142] Below, refer to Figure 1 Each layer is described.
[0143] <Base Material>
[0144] 《First substrate composed of a metal substrate》
[0145] From the perspective of improving the followability to asphalt and other road surfaces, the first substrate 12 composed of a metal substrate used in the marking sheet of the present invention is preferably a metal foil. The metal foil is not particularly limited, but from the perspective of price and easy availability, aluminum foil, copper foil, iron foil, and stainless steel foil are preferably used, and among them, aluminum foil that is easily deformed by hammering is preferably used.
[0146] The thickness of the metal foil is preferably about 10 to 100 μm, more preferably about 20 to 90 μm. When the thickness of the metal foil is within the above range, the metal foil is easily deformed during hammering for attachment to the road surface and easily follows the irregularities of asphalt.
[0147] Second Base Material
[0148] The second base material 14 is a base material for forming other layers such as a decorative layer or a protective layer described later.
[0149] The material of the second substrate 14 is not particularly limited, and examples thereof include plastic substrates, glass, woven fabrics, nonwoven fabrics, and paper. Examples of plastic substrates include polyvinyl chloride (PVC), polycarbonate (PC), polymethyl methacrylate (PMMA), polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polyimide, acrylonitrile-butadiene-styrene copolymer (ABS), and polyamide (nylon). Among them, polyvinyl chloride, polyethylene terephthalate, polyethylene, and polyimide are preferred from the perspective of being easy to print and mark with a desired color when applying ink and being easily available industrially.
[0150] The thickness of the second substrate 14 is preferably about 30 to 300 μm, more preferably about 50 to 250 μm. The thickness of the second substrate within the above range is not a hindrance to pedestrians, etc., and can exhibit the required strength.
[0151] In addition, as the second substrate 14, for example, Figure 1 A plurality of substrates may be stacked in the same manner as a third substrate is stacked in the middle, and in this case, the plurality of substrates may be the same or different.
[0152] <Adhesive Layer>
[0153] 《First adhesive layer》
[0154] The first adhesive layer 11 is formed using the adhesive composition of the present invention. For example, the adhesive layer can be obtained by performing a crosslinking reaction in the adhesive composition, specifically, by crosslinking the (meth)acrylic copolymer (A) with a crosslinking agent (C).
[0155] The conditions for forming the first adhesive layer 11 are as follows, for example. The adhesive composition of the present invention is applied to a substrate or a release-treated surface of a release liner, and the coating film is formed by drying the coating film at 50 to 150° C., more preferably 60 to 100° C., preferably for 1 to 10 minutes, more preferably for 2 to 7 minutes, although the conditions vary depending on the type of solvent. The film thickness of the dried coating film is preferably 5 to 125 μm, more preferably 10 to 100 μm.
[0156] The first adhesive layer 11 is preferably formed under the following conditions. The adhesive composition of the present invention is applied to a substrate or a release-treated surface of a release liner, and a release liner is attached to the coating formed under the above conditions, and then the coating is preferably cured at 23°C and 50% RH for 7 days or more, and more preferably cured at 40°C for 3 to 5 days. Crosslinking under the above-mentioned aging conditions can efficiently form a crosslinked body.
[0157] The adhesive composition may be applied by a known method such as spin coating, knife coating, roll coating, bar coating, doctor blade coating, die coating, or gravure coating to a predetermined thickness and then dried.
[0158] 《Second adhesive layer》
[0159] The second adhesive layer 13 can be formed with the same or different adhesive composition of the present invention, or can be formed with other adhesive compositions. In addition, when multiple substrates are stacked after the second substrate 14, the adhesive compositions used to form the adhesive layers stacked with each substrate can also be the same or different.
[0160] The thickness of each adhesive layer is not particularly limited, but is preferably 5 to 125 μm, more preferably 10 to 100 μm.
[0161] Other Layers
[0162] Other layers may be stacked on the second substrate 14 as needed, such as other adhesive layers, decorative layers, metal layers, coloring layers, printing layers, protective layers, etc.
[0163] The above-mentioned other layers may be composed of a single layer or a plurality of layers. In addition, the decorative layer does not necessarily have to be formed on the entire surface of the second substrate, but may be formed only in a predetermined area of the second substrate.
[0164] The thickness of the other layer is not particularly limited, but is preferably about 30 to 300 μm, more preferably about 50 to 250 μm. When the thickness of the other layer is within the above range, the required strength can be achieved without hindering pedestrians.
[0165] (Decorative layer)
[0166] The decorative layer is a layer for providing a desired pattern, color, character, etc. to the road surface or ground marking sheet in order to provide a desired advertisement, guidance display, or the like.
[0167] The method for forming the decorative layer varies depending on the type of the decorative layer. For example, when the decorative layer is composed of an ink layer (printing layer), the decorative layer can be formed by relief printing such as flexographic printing, gravure printing such as photogravure printing, flat printing such as offset printing, screen printing such as screen printing, printing by various printers such as inkjet printers, etc. In the case where the decorative layer is composed of a coating layer, for example, the decorative layer can be formed by a coating machine such as a roll coater, a knife coater, a roll blade coater, an air knife coater, a die coater, a rod coater, a gravure coater, a curtain coater, a spray coater, a spray gun, etc. Furthermore, when the decorative layer is composed of a transfer from a transfer sheet, the decorative layer can be formed by applying pressure to the transfer sheet laminated on the surface of the substrate, or by heating the transfer sheet laminated on the surface of the substrate, etc., depending on the type of the transfer sheet. Furthermore, when the decorative layer is composed of a metal film, the decorative layer can be formed by evaporation, sputtering, etc.
[0168] (Protective layer)
[0169] The protective layer is formed by laminating a film of a resin such as polyester such as polyethylene terephthalate (PET), polyvinyl chloride, polyimide, polyurethane, acrylic resin, epoxy resin, fluororesin, etc. directly or via a bonding layer onto a layer constituting the decorative laminate film, or can be formed by coating a resin composition on the surface of the film layer and drying it.
[0170] <Release Liner>
[0171] The release liner 10 used in the marking sheet of the present invention is used to prevent the adhesive layer from sticking to a portion other than the intended surface to which the marking sheet of the present invention is attached, and is provided on the first adhesive layer (11) in the form of a marking sheet before being placed on a road surface, etc.
[0172] The release liner is not particularly limited, and a known release liner can be suitably used. Examples of the release liner include a release liner obtained by coating a release agent on a resin film such as paper or polyester.
[0173] As the release agent, although it depends on the material of the pressure-sensitive adhesive layer, a known release agent can be used, and examples thereof include a silicone-based release agent and a fluorine-based release agent.
[0174] <Application of road or ground marking sheets>
[0175] In addition to its ability to follow rough surfaces such as asphalt, the marking sheet of the present invention also has excellent adhesion, weather resistance, heat resistance and moisture and heat resistance. When peeled off, the adhesive is not easily transferred from the substrate to the adherend, so it can be suitable for uses that require these physical properties (for example, when the marking sheet is used to apply temporary markings on asphalt in parking lots, roads and construction sites used by cars, large trucks, etc., or when the marking sheet needs to be temporarily attached to the ground with a large number of pedestrians indoors and outdoors, etc.).
[0176] Example
[0177] The present invention will be specifically described below based on Examples, but the present invention is not limited to these Examples. In the following descriptions of Examples, etc., "parts" means "parts by mass" unless otherwise specified.
[0178] The methods for measuring physical properties are as follows.
[0179] [Weight average molecular weight (Mw) and number average molecular weight (Mn), ratio of components having a molecular weight of 5,000 or less in the (meth)acrylic acid-based copolymer]
[0180] For the (meth)acrylic copolymers of the synthesis examples, the differential molecular weight distribution curve and the integrated molecular weight curve were obtained by gel permeation chromatography (GPC) under the following conditions. Mw and Mw / Mn were obtained from the differential molecular weight distribution curve, and the proportion of components with a molecular weight of 5,000 or less was obtained from the integrated molecular weight distribution curve.
[0181] ·Measurement device: HLC-8120GPC (manufactured by Tosoh Corporation)
[0182] ·GPC column configuration: The following 5 columns (all manufactured by Tosoh Corporation)
[0183] (1)TSKgel HxL-H (guard column)
[0184] (2)TSKgel G7000HXL
[0185] (3)TSKgel GMHxL
[0186] (4)TSKgel GMHxL
[0187] (5)TSKgel G2500HXL
[0188] Flow rate: 1.0mL / min
[0189] Column temperature: 40℃
[0190] Sample concentration: 1.5% (w / v) (diluted with tetrahydrofuran)
[0191] Mobile phase solvent: tetrahydrofuran
[0192] · Standard polystyrene conversion
[0193] [Synthesis Example A-1]
[0194] In a flask equipped with a stirring device, a nitrogen inlet tube, a thermometer and a reflux cooling tube, 40.5 parts of n-butyl acrylate (BA), 56 parts of 2-ethylhexyl acrylate (2EHA), 3.5 parts of acrylic acid (AA), and 100 parts of ethyl acetate were added, and the contents of the flask were heated to 70°C while introducing nitrogen into the flask. Then, 0.05 parts of 2,2'-azobisisobutyronitrile (hereinafter also referred to as "AIBN") were added to the flask while stirring. Heating and cooling were performed for 5 hours so that the temperature of the contents in the flask could be maintained at 70°C. After the temperature was raised to 78°C, reflux reaction was performed for 2 hours to obtain a (meth)acrylic acid copolymer (A-1). After the reaction was completed, it was diluted with ethyl acetate to obtain a polymer solution having a solid content concentration of 30% by mass containing the (meth)acrylic acid copolymer (A-1). The obtained (A-1) had a Mw of 890,000 as measured by GPC, a Mw / Mn of 5.2, and a ratio of components having a molecular weight of 5,000 or less was 0.1% by mass.
[0195] [Synthesis Examples A-2 to A-10]
[0196] (Meth)acrylic acid-based copolymers (A-2) to (A-10) were prepared in the same manner as in Synthesis Example A-1 except that the raw materials shown in Table 1 were used.
[0197] [Synthesis Example A-11]
[0198] In a flask equipped with a stirring device, a nitrogen inlet tube, a thermometer and a reflux cooling tube, 40.5 parts of n-butyl acrylate (BA), 56 parts of 2-ethylhexyl acrylate (2EHA), 3.5 parts of acrylic acid (AA), and 140 parts of ethyl acetate were added, and the contents of the flask were heated to 70°C while introducing nitrogen into the flask. Then, 0.05 parts of AIBN were added to the flask while stirring. Heating and cooling were performed for 5 hours so that the temperature of the contents in the flask could be maintained at 70°C. During this period, 0.05 parts of AIBN were added 10 minutes after the start of the reaction, 0.05 parts of AIBN were added 20 minutes later, and 0.05 parts of AIBN were added 30 minutes later. Thereafter, the temperature was raised to 78°C, and reflux reaction was performed for 2 hours to obtain a (meth)acrylic acid copolymer (A-11). After the reaction was completed, it was diluted with ethyl acetate to obtain a polymer solution containing a (meth)acrylic acid copolymer (A-11) with a solid content concentration of 30% by mass. The obtained (A-11) had a Mw of 420,000 as measured by GPC, a Mw / Mn of 9.0, and a ratio of components having a molecular weight of 5,000 or less was 1.7% by mass.
[0199] Table 1
[0200]
[0201] The symbols of the monomer components in Table 1 mean the following.
[0202] BA: n-butyl acrylate
[0203] t-BA: tert-butyl acrylate
[0204] 2EHA: 2-Ethylhexyl acrylate
[0205] i-OA: Isooctyl acrylate
[0206] AA: Acrylic acid
[0207] [Example 1]
[0208] The polymer solution (solid content concentration 30% by mass) obtained in Synthesis Example A-1, DP-2669 (manufactured by Harima Chemicals Group, Ltd.: rosin-based tackifier resin, softening point 135°C) as a tackifier resin, and L-45K (manufactured by Soken Chemical Co., Ltd.: isocyanate crosslinker, solid content concentration 45% by mass) as a crosslinking agent were mixed in an amount of 100 parts of A-1, 20 parts of DP-2669, and 1.5 parts of L-45K in a solid content ratio to obtain an adhesive composition.
[0209] [Examples 2 to 9, Comparative Examples 1 to 10]
[0210] An adhesive composition was prepared in the same manner as in Example 1 except that the mixing composition of the adhesive composition was changed to that shown in Table 2 or Table 3. In addition, the numerical values in the columns of each component in Table 3 and Table 4 represent parts by mass.
[0211] [Manufacturing of marking sheets]
[0212] The obtained adhesive composition is used to form a first adhesive layer with a thickness of 30 μm after drying on a release-treated liner, an aluminum substrate (50 μm thick) is formed thereon as a first substrate, an adhesive layer with a thickness of 50 μm after drying is formed thereon using the same adhesive composition as the first adhesive as a second adhesive, and a PVC substrate (50 μm thick) is further laminated thereon as a second substrate, thereby producing a marking sheet for evaluation.
[0213] [Evaluation method]
[0214] The evaluations of (1) heat resistance, (2) moisture and heat resistance, (3) adhesion to metal substrates, (4) peeling resistance based on a road surface adhesion test, (5) re-peelability after a road surface adhesion test, and (6) adhesion were performed. The evaluation methods are as follows. The evaluation results are shown in Tables 2 and 3.
[0215] (1) Evaluation of heat resistance
[0216] A marking sheet was pasted on a polished SUS and allowed to stand at 80°C for 7 days and then at 23°C / 50% RH for 30 minutes. The peeling morphology when peeled from the adherend at a peeling angle of 180° and a tensile speed of 300 mm / min was visually observed and evaluated according to the following criteria.
[0217] (Evaluation Criteria)
[0218] ○: The transfer area of the adhesive is less than 1%.
[0219] △: The transfer area of the adhesive is 1% or more and less than 20%.
[0220] ×: The transfer area of the adhesive is 20% or more.
[0221] (2) Evaluation of moisture resistance
[0222] A marking sheet was pasted on a polished SUS and allowed to stand at 60°C / 95% RH for 7 days and then at 23°C / 50% for 30 minutes. The peeling morphology when peeled from the adherend at a peeling angle of 180° and a tensile speed of 300 mm / min was visually observed and evaluated according to the following criteria.
[0223] (Evaluation Criteria)
[0224] ○: The transfer area of the adhesive is less than 1%.
[0225] △: The transfer area of the adhesive is 1% or more and less than 20%.
[0226] ×: The transfer area of the adhesive is 20% or more.
[0227] (3) Evaluation of adhesion to metal substrates
[0228] The pressure-sensitive adhesive layer was rubbed with a finger, visually observed, and evaluated based on the following criteria.
[0229] (Evaluation Criteria)
[0230] ○: No peeling or other changes were observed even after rubbing with a finger 30 times or more.
[0231] △: Peeling occurred after rubbing with a finger 11 to 30 times.
[0232] ×: Peeling occurred within 10 rubs with a finger.
[0233] (4) Evaluation of peeling resistance based on road adhesion test
[0234] After cleaning the asphalt road surface, a marking sheet cut into a size of 10 cm x 15 cm was pasted on the road surface by hand and compacted with a rubber hammer. The peeling state of the marking sheet after 3 months was visually observed and evaluated according to the following criteria.
[0235] (Evaluation Criteria)
[0236] ○: No peeling at all.
[0237] △: Peeling or lifting was observed at the edge.
[0238] ×: peeled off.
[0239] (5) Evaluation of removability after pavement adhesion test
[0240] After cleaning the asphalt road surface, a marking sheet cut into a size of 10 cm x 15 cm was pasted on the road surface by hand and compacted with a rubber hammer. The peeling state of the marking sheet after peeling off after 3 months was visually observed and evaluated according to the following criteria.
[0241] (Evaluation Criteria)
[0242] ○: The transfer area of the adhesive is less than 1%.
[0243] △: The transfer area of the adhesive is 1% or more and less than 20%.
[0244] ×: The transfer area of the adhesive is 20% or more.
[0245] (6) Evaluation of Adhesion
[0246] The marking sheet was attached to the polished SUS and allowed to stand for 20 minutes at 23°C / 50%RH. The adhesive strength (N / 25 mm) when peeled from the adherend at a peeling angle of 180° and a tensile speed of 300 mm / min was evaluated.
[0247] Table 2
[0248]
[0249] Table 3
[0250]
[0251] The tackifying resins in Tables 2 and 3 are detailed as follows.
[0252] DP-2669 ("HARITACK DP-2669" manufactured by Harima Chemicals Co., Ltd.; rosin-based tackifying resin, softening point 135°C)
[0253] D-135 ("PENSEL D-135" manufactured by Arakawa Chemical Industries, Ltd.; rosin-based tackifying resin, softening point 135°C)
[0254] D-160 ("PENSEL D-160" manufactured by Arakawa Chemical Industries, Ltd.; rosin-based tackifying resin, softening point 160°C)
[0255] FTR-6100 (Made by Mitsui Chemicals, Inc.; styrene-based tackifier resin, softening point 100°C)
[0256] D-125 ("PENSEL D-125" manufactured by Arakawa Chemical Industries, Ltd.; rosin-based tackifying resin, softening point 125°C)
[0257] SEA-100 ("SUPER ESTER A-100" manufactured by Arakawa Chemical Industries, Ltd.; rosin-based tackifying resin, softening point 100°C)
[0258] L-45K (manufactured by Soken Chemical Co., Ltd.; isocyanate crosslinking agent)
[0259] As can be seen from Table 2, the marking sheets obtained from Examples 1 to 9 not only maintain the adhesion to the substrate and the adhesion to the road surface required as adhesive properties, but also have excellent stress relaxation properties under high temperature and high humidity environments. Furthermore, when peeled off from the road surface, little adhesive residue remains on the road surface, that is, the re-peelability from the road surface is excellent.
[0260] The marking sheets of Comparative Examples 1 and 2 using a rosin-based tackifier resin having a softening point of less than 120°C, the marking sheets of Comparative Examples 3 to 5 in which the blending amount of the rosin-based tackifier resin having a softening point of more than 120°C is outside the range specified in the present invention, the marking sheets of Comparative Examples 6 to 9 in which the contents of various monomers are outside the range specified in the present invention, and the marking sheet of Comparative Example 10 in which the proportion of the component with a molecular weight of 5,000 or less in the (meth)acrylic copolymer (A) is outside the range specified in the present invention all showed poor results in terms of adhesive properties.
[0261] Explanation of symbols
[0262] 10: Adhesive or release liner
[0263] 11: First adhesive layer
[0264] 12: First substrate composed of a metal substrate
[0265] 13: Second adhesive layer
[0266] 14: Second base material made of polyvinyl chloride
[0267] 15: The third adhesive layer
[0268] 16: A third substrate made of polyimide.
Claims
1. A road surface or ground marking sheet, comprising an adhesive layer formed from an adhesive composition comprising a (meth)acrylic acid copolymer (A) and a rosin-based tackifier resin (B) and a metal substrate, The (meth)acrylic copolymer (A) is a copolymer comprising monomer components of 20 to 69% by mass of a (meth)acrylic acid alkyl ester monomer (a1) having an alkyl carbon number of 1 to 7, 30 to 74% by mass of a (meth)acrylic acid alkyl ester monomer (a2) having an alkyl carbon number of 8 to 20, and 1 to 6% by mass of an acidic group-containing monomer (a3), wherein the total of the components (a1) to (a3) is 100% by mass. The content of the rosin-based tackifier resin (B) is 10 to 30 parts by mass relative to 100 parts by mass of the (meth)acrylic copolymer (A). The proportion of the component having a molecular weight of 5000 or less in the (meth)acrylic copolymer (A) is 1.5% by mass or less, The softening point of the rosin-based tackifying resin is above 120°C.
2. The road surface or ground marking sheet according to claim 1, wherein: It also contains a cross-linking agent (C).
3. The road surface or ground marking sheet according to claim 1, wherein: The metal substrate is aluminum foil.
4. The road surface or ground marking sheet according to claim 1 or 3, wherein: Also has a plastic substrate.
5. The road surface or ground marking sheet according to claim 4, wherein: The plastic substrate is at least one substrate selected from polyvinyl chloride, polyethylene terephthalate, polyethylene and polyimide.
Citation Information
Patent Citations
Adhesive composition for hard-to-bond adherend, adhesive for hard-to-bond adherend and adhesive tape for hard-to-bond adherend
JP2019151837A
Adhesive composition and adhesive sheet
CN108690536A
Road surface / floor surface marking laminate sheet and road surface / floor surface marking sheet
JP2015184488A